Starhenge. Book 1, The dragon and the boar - Sharp, Liam; Sharp, Liam (Image Comics, 2023)
"A future MERLIN travels to 5th century Britain to prevent monstrous time-travelling killer robots robbing the universe of magic! Amber Weaver's lively present-day narrative reveals how she becomes drawn into a war across time... TERMINATOR meets THE GREEN KNIGHT in this enthralling epic inspired by the ARTHURIAN sagas!"--Amazon.